Derivational Suffixes in the Reading Textbook of Sixth Grade Elementary School by Evan Moor - I Gede Arya Wiranata; IGB Wahyu Nugraha Putra (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2024)
This study focuses on derivational suffixes that are found in textbook "Sixth Grade Elementary School" by Evan Moor. This project aims to discover the types and process of derivational suffixes in the data source, the data was collected using an observation method, and it was analyzed using a descriptive qualitative approach. The data used in this research were analyzed using theory from Plag (2003) and McCarthy (2002). The study identified four main types of derivational suffixes: nominal, verbal, adjectival, and adverbial suffixes. A total of 98 data derivational suffixes were identified. The research revealed that nominal suffixes were the most common at 58 data of suffixes included -er, -ing, -ment, -ion, -ance, -ence, and -ness. Followed by adjectival suffixes accounted 22 data, comprise suffixes like -ly, -al, -able/-ible, -ful, -ous, -less, -ive, and -ish. Adverbial suffixes with 15 instances characterized by the suffix -ly. Verbal suffixes was the least frequently found in the data analysis at 3 represented by -ize. Based on the finding indicate that derivational suffixes as the most dominant, it is relevant with the theory which is explain that the number of nominal suffixes were frequently than other suffixes. The process of derivational suffixes which is described with flat structure it really help to decide the changing of word class process happen in the data.